Biogeochemical behavior of P in the soil and porewater of a low-salinity estuarine wetland: Availability, diffusion kinetics, and mobilization mechanism. (1st July 2022) - Hu, Minjie; Sardans, Jordi; Le, Yixun; Yan, Ruibing; Zhong, Yi; Huang, Jiafang; Peñuelas, Josep; Tong, Chuan
Highlights: DGT/HR-Peeper/DIFS was designed to measure P-Fe-S dynamics in estuarine wetlands. Labile and soluble P showed high variation and was higher in plant dormant period. High diffusion and supply capacity accelerated P mobilization in brackish wetlands. Release and kinetics of P are mainly regulated by the Fe-coupled mobilization of P. Abstract: Estuarine wetlands, which typically store large amounts of phosphorus (P), are experiencing increased salinity as well as changed environmental factors caused by rising sea levels. In this study, the seasonal dynamics of P speciation, availability, and biogeochemical couplings with iron (Fe)-sulfur (S) in soil and porewater were measured in a low-salinity estuarine wetland using in situ high-resolution diffusive gradients in thin films (DGT) and dialysis (HR-Peeper) techniques. The diffusion kinetics and resupply capacity of P from the soil phase to solution were simulated using a DGT-induced fluxes in soils (DIFS) model. The transition from freshwater to brackish wetlands reduced soil P pools and shifted to more recalcitrant speciation. The concentration of DGT-labile P across the soil-water profiles ranged from 0.002 to 0.039 (mean: 0.015) mg L −1, which increased with increasing salinity in both the field and mesocosm experiments. The distributions of labile and soluble P showed high heterogeneity across the profiles, and there were some sharp peak values below the soil-water interface (SWI), which significantly increased the concentration and lability of P. The strong coupling between labile P and Fe (S) provided direct evidence for the coexistence of iron reduction (IR) and sulfate reduction (SR) in the estuary, while IR might predominate in P mobilization in the brackish environment because of higher labile Fe concentrations and stronger Fe-P couplings. The diffusion fluxes of P were positive at both sites, demonstrating that the kinetics of P were from the soils to the overlying water. Higher R and k -1 values fitted in the DIFS model implied that a stronger resupply capacity and desorption rate and thus faster remobilization kinetics of P occurred with increasing salinity. Our findings indicated that increased salinity (even at low levels) can alter the desorption rate and resupply capacity of soil P in estuarine wetlands and accelerate P remobilization and release by regulating the IR and SR processes, thereby leading to the deterioration of water quality. Graphical abstract: Image, graphical abstract .